Influence of Tariquidar, an ABC Transporter Inhibitor, on the Ca2+-Dependent Mitochondrial Permeability Transition Pore - Tatiana A. Fedotcheva; Alexey G. Kruglov; Nadezhda I. Fedotcheva (Pharmaceuticals)
Background: Tariquidar (Tq) is an inhibitor of the multidrug resistance (MDR) proteins relevant to ATP-binding cassette transporters (ABC transporters), which suppresses the ATP-dependent efflux of a variety of hydrophilic and amphipathic compounds, including anticancer drugs. Tq is a representative of a new generation of MDR inhibitors with high affinity to ABC proteins. However, there are still no data on the possible effect of Tq on mitochondria as an important target in the regulation of cell death or survival. Methods: We investigated the influence of Tq on the Ca2+-dependent mitochondrial permeability transition pore (mPTP). The effect of Tq was assessed using several parameters, including the calcium load, membrane potential, and mitochondrial swelling. To evaluate the specific targets of Tq, selective inhibitors of components of the mitochondrial pore were used, including adenine nucleotides, carboxyatractylozide (Catr) and bongkrekic acid (BA), oligomycin, and cyclosporine A. Results: Tq decreased the calcium retention capacity, activated mitochondrial swelling, and lowered the influence of ADP and ATP, the inhibitors of the Ca2+-induced pore opening, at their low concentrations. These effects of Tq were observed in both calcium-load and swelling assays, thus mimicking the effect of Catr, a selective inhibitor of adenine nucleotide translocase (ANT). Tq also decreased the protective effect of BA, an inhibitor of ANT and mPTP, on the calcium retention capacity of mitochondria. Further, Tq dose-dependently decreased the inhibitory effect of a low ATP concentration but not of high concentrations, at which the effect of Tq was activated by oligomycin, an inhibitor of F-ATP synthase. Conclusions: The influence of Tq extends to mitochondria, specifically to the regulation of membrane permeability, promoting the activation of pore opening, probably through an interaction with ANT, a component of the pore-forming complex. The effect of Tq on the opening of mPTP is strongly dependent on the concentrations of adenine nucleotides and, consequently, on the functional state of mitochondria. The direct influence of Tq on mitochondria can be considered as a new activity that promotes the sensitization of cells to various treatments and stimuli.